A review on the use of polypropylene fiber in concrete and bibliometric analysis - Tanash, Alaa Omar; Khairunisa, Muthusamy; Shahrul Niza, Mokhatar; Fahrizal, Zulkarnain; Sofia Adibah, Jasni (Penerbit Akademia Baru, 2025)
The use of polypropylene fibres (PF) has aroused great interest in science and the construction industry. This is mainly due to the numerous benefits they offer in terms of sustainability relative to steel fibres and steel fabrics. This study provides a comprehensive assessment of the current state of knowledge and technological advances in the use of PF to enhance the strength of concrete. A comprehensive analysis of the impacts of PF on the fresh and mechanical properties of concrete is presented. The effects of PF on various aspects of durability such as water absorption, chloride penetration, sulphate resistance, drying shrinkage, carbonation resistance and fire resistance are also reviewed. The workability of concrete is impacted by the addition of PF. The formation and progression of initial microcracks is reduced in concrete containing PF. Use of PF significantly improves the tensile and flexural strength of concrete. Concrete produced using PF demonstrate better sulphate, chloride and fire resistance properties. Further research on its use as sole fibre or blended with other types of fibre in modern concretes and blended cement concrete remains to be discovered.